IbM LITERASI MEDIA DI BENGKULU - Mona Ardina; Gushevinalti Gushevinalti; Bustanuddin Lubis (Universitas Bengkulu, 2018)
Literacy on children in Bengkulu is still relatively low. This aspect is feared to have negative impact on children as young generation who frequently become the media consumer. While children's access to the media is very broad. At this activity, the partners are Islamic Kindergarten of Baitul Izzah and Dellia Creative School. In the first activity, the children/students are introduced to media literacy through simulations by showing them TV serials, commercials, and adult songs as well as fun education games. While besides the school components which are children/students and teacher, this activity also invites parents to recognize media literacy through training and simulation. Outcomes and targets of this activity synergically with methods for implementing media literacy activities that result in increased teacher competence in understanding media literacy and the implementation of media literacy in the curriculum of Kindergarten/Early Childhood Education. This activity is carried out by administering workshop for teachers while the parents are given training and simulation about media literacy. The main part is the children's understanding of the negative effects of media for children can be improved through several simulations and games with fun education based. Implementation of media literacy in Kindergarten/Early Childhood Education is conducted with the assistance by the implementation team until the teacher can independently apply the activities by themselves in learning process at school. The end result of this activity is Media Literacy handbook that can be used by teachers and parents. Keywords: Media Literacy, Teachers, Parents, Children, Simulation.